Pathological and Microbiological Investigations on Lung Lesions of Slaughtered Broilers in the Slaughterhouse - Timurkaan, Necati; Yilmaz, Fethi; Kilic, Ayse; Ozbey, Gokben (Medwell Online, 2008)
The purpose of this study was to identify the pathologic and microbiologic findings and their ratios, which were detected in the lungs of broilers slaughtered in slaughterhouse. For this purpose, lung tissues of 21,600 animals, which were slaughtered in a commercial broiler slaughterhouse were examined and the tissues in which lesions were observed, underwent microbiologic and histopathological examination. In 275 (1.27%) of the examined broilers, pathologic lesions were detected and in 244 of these samples, different bacterial agents were identified. All of the histopathological findings detected in the lungs had an inflammatory nature and when they were categorized according to predominant features in the inflammation area, exudative inflammation in 241 broilers (87.63%), proliferative inflammation in 24 (8.72%) and exudative-proliferative (bronchointersititiel) inflammation in 10 (3.63%) were seen. In all of the cases, peribronchial and perivascular lymphoid hyperplasia and osseous and cartilaginous nodules in parenchyma of the lungs appeared as common findings. It was found that among the microbiologically identified agents, E.coli ranked first. No clear relation between the type of lesions and the infectious agents identified was established. In conclusion, these results indicated that the ratio of lung lesions were 1.27% in slaughtered broiler chickens.
Keywords: Broiler chicken; slaughterhouse; lungs; pathology; microbiology